Antioxidant, anti-collagenase, and antibacterial activities of Fucus vesiculosus silver nanoparticles - Savitri, Evika S.; Rahmawaty, Annisa E.; Minarno, Eko B. (Narra J, 2024)
Fucus vesiculosus is an alga with high fucoxanthin, phlorotannin, fucoidan, sterol, and astaxanthin. The silver nanoparticles of F. vesiculosus (AgNPs-Fv) are expected to have high antioxidant, anti-collagenase, and antibacterial activities. The aim of this study was to characterize the distribution and size of AgNPs-Fv and determine their antioxidant, anti-collagenase, and antibacterial activities. The distribution and size of AgNPs-Fv were measured using particle size analyzer (PSA) analysis. The nanoparticle compound and their functional groups were characterized using a scanning electron microscope (SEM) and Fourier-transform infrared spectroscopy (FTIR), respectively. The antioxidant activity of AgNPs-Fv was determined using a 1.1-diphenyl-2-picrylhydrazyl (DPPH) assay, while the anti-collagenase activity was examined using the spectrophotometric method. The antibacterial activity was assessed using an inhibition zone test, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC). Results indicated that the AgNPs-Fv had a dominant volume of about 86.3% with a diameter of 113.3 nm. SEM analysis revealed the spherical AgNPs with sizes between 27 and 54 nm. The FTIR analysis of the AgNPs-Fv absorption band at 1,046 cm-1 demonstrated the bond between the Ag metal and the O-H hydroxyl group. The antioxidant activity of AgNPs-Fv was higher than F. vesiculosus extract (24.23±3.55 mg/L vs 47.45±3.16 mg/L). AgNPs-Fv also had a higher anti-collagenase activity compared to F. vesiculosus extract (66.74±6.352 mg/L vs 145.1±6.326 mg/L). The inhibition zone diameter of AgNPs-Fv was greater than F. vesiculosus extract. The MIC and MBC of AgNPs-Fv were 18.75 and 18.75 ppm, while F. vesiculosus extract was 37.5 and 75 ppm, respectively. These results suggested that AgNPs of F. vesiculosus had higher antioxidant, anti-collagenase, and antibacterial activities than F. vesiculosus extract alone.